Liver immunopathogenesis in fatal cases of dengue in children: detection of viral antigen, cytokine profile and inflammatory mediators - Moragas, Leandro Junqueira; Alves, Felipe de Andrade Vieira; Oliveira, Lucca de Lima Siqueira; Salomão, Natália Gedeão; Azevedo, Caio Gonçalves; da Silva, Jemima Fuentes Ribeiro; Basílio-de-Oliveira, Carlos Alberto; Basílio-de-Oliveira, Rodrigo; Mohana-Borges, Ronaldo; de Carvalho, Jorge José; Rosman, Fernando Colonna; Paes, Marciano Viana; et al. (Frontiers in Immunology, 2023)
Dengue virus (DENV), the etiologic agent of dengue fever illness, represents a global public health concern, mainly in tropical and subtropical areas across the globe. It is well known that this acute viral disease can progress to severe hemorrhagic stages in some individuals, however, the immunopathogenic basis of the development of more severe forms by these patients is yet to be fully understood. In this context, we investigated and characterized the histopathological features as well as the cytokine profile and cell subpopulations present in liver tissues from three fatal cases of DENV in children. Hematoxylin and Eosin, Periodic Acid Schiff and Picro Sirius Red staining were utilized for the histopathological analysis. Immunohistochemistry assay was performed to characterize the inflammatory response and cell expression patterns. Vascular dysfunctions such as hemorrhage, vascular congestion and edema associated with a mononuclear infiltrate were observed in all three cases. Liver tissues exhibited increased presence of CD68 + and TCD8 + cells as well as high expression of MMP-9, TNF-α, RANTES, VEGFR-2 mediators. Viral replication was confirmed by the detection of NS3 protein. Taken together, these results evidenced key factors that may be involved in the development of severe alterations in liver tissues of children in response to DENV infection.Material and methodsAll procedures performed during this study were approved by the Ethics Committee of the Oswaldo Cruz Foundation/FIOCRUZ (CAEE: 47525115.3.0000.5248).